Flexible, sandwich-like CNTs/NiCo2O4 hybrid paper electrodes for all-solid state supercapacitors. Issue 12 (7th March 2017) - Zheng, Yongjia; Lin, Zhiqiang; Chen, Wenjun; Liang, Binghao; Du, Huiwei; Yang, Rongliang; He, Xianfeng; Tang, Zikang; Gui, Xuchun
Abstract : With the increasing demand for compact storage systems for portable and wearable electronic devices, flexible supercapacitors with high volumetric performance have attracted considerable attention. Abstract : With the increasing demand for compact storage systems for portable and wearable electronic devices, flexible supercapacitors with high volumetric performance have attracted considerable attention. Here, we report a simple method to fabricate a sandwich-like carbon nanotubes (CNTs)/NiCo2 O4 hybrid paper electrode, consisting of a layer of conductive CNT buckypaper coated with honeycomb-like NiCo2 O4 nanosheets at both sides. Owing to the high conductivity of the CNT skeleton and vertically aligned structure of NiCo2 O4 nanosheets, the free-standing hybrid paper possesses an ultra-high specific capacitance of 1752.3 F g −1 and excellent cycling performance. A flexible all-solid-state symmetrical supercapacitor has been further assembled based on the hybrid paper. The device exhibits excellent volumetric energy and power densities (1.17 mW h cm −3 and 2430 mW cm −3 ) and deformability, even under bending at an angle of 180°. The hybrid paper can serve as a freestanding and flexible electrode for various energy devices.